Psychosocial responses during different phases of sport-injury rehabilitation: a qualitative study - Clement, D.; Arvinen-Barrow, M.; Fetty, T. (Journal of Athletic Training, 2015)
Context: Athletic trainers have traditionally conceptualized rehabilitation programs in terms of 3 distinct physiologic phases; however, these phases appear to neglect athletes' psychosocial responses to their injuries.